2020
DOI: 10.2147/ott.s229957
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA DANCR Promotes Sorafenib Resistance via Activation of IL-6/STAT3 Signaling in Hepatocellular Carcinoma Cells</p>

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the major malignancies and the second most common cause of cancer-related death worldwide. Sorafenib, an approved first-line systematic treatment agent for HCC, is capable to effectively improve the survival of patients with advanced HCC. The long-noncoding RNA (lncRNA) differentiation antagonizing non-protein coding RNA (DANCR) has been reported to exert oncogenic functions in several kinds of human cancers. However, the role of lncRNA DANCR in sorafenib re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…This is in agreement with former studies that show the aberrant upregulation of DANCR in HCC and the involvement of DANCR dysregulation in HCC progression. 26,27 Furthermore, this study confirmed that DANCR knockdown greatly inhibits Huh7 and HepG2 cell proliferation and increases cell apoptosis, which is consistent with the previous study. 28 The anti-apoptosis effect of DANCR can also found in cholangiocarcinoma, which showed that suppression of DANCR could induce the expression of cleaved-caspase-3 and promote apoptosis both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with former studies that show the aberrant upregulation of DANCR in HCC and the involvement of DANCR dysregulation in HCC progression. 26,27 Furthermore, this study confirmed that DANCR knockdown greatly inhibits Huh7 and HepG2 cell proliferation and increases cell apoptosis, which is consistent with the previous study. 28 The anti-apoptosis effect of DANCR can also found in cholangiocarcinoma, which showed that suppression of DANCR could induce the expression of cleaved-caspase-3 and promote apoptosis both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…It was implicated that DANCR played an essential role in HCC progression. For example, a high level of DANCR was associated with stemness features (Yuan et al, 2016), metastasis (Wen et al, 2020), and chemotherapeutic drug resistance in HCC (Liu et al, 2020a). In addition, the ROC (receiver operating characteristic) analysis showed that plasma DANCR and exosomal DANCR exhibited good discriminatory ability, suggesting it could be a promising diagnostic marker (Ma et al, 2016;Wang S.C. et al, 2020; Table 2).…”
Section: Hepatocellular Carcinomamentioning
confidence: 98%
“…For example, DANCR was verified to interact with 3 UTR of CTNNB1 mRNA in hepatocellular carcinoma, thus competitively blocking miRNA site and reversing miRNA-mediated CTNNB1 suppression (Yuan et al, 2016). Similarly, in sorafenib-resistant HCC, DANCR could bind with PSMD10 mRNA to stabilize its expression via blocking the miRNA binding site (Liu et al, 2020a). In the case of binding to proteins, it is interesting that DANCR could regulate both protein stability (Wen et al, 2020) and protein degradation (Xie et al, 2020).…”
Section: Regulatory Mechanisms For Dancrmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating multiple datasets from these databases can provide a high degree of evidence from various studies in different populations using either raw or processed data, such as the Gene Expression Omnibus (GEO) ( accessed on 1 February 2021), a biomedical repository providing transcriptomic datasets for both microarray and next-generation sequencing platforms [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Changes in the mRNA expression levels of genes, sometimes an order of magnitude higher or lower in tumors than in normal matched tissues, illustrate, respectively, their roles as either oncogenes or tumor suppressors in cancer [ 33 , 34 , 35 ]. Applying this concept to BRCA and PSMA family genes, we used multiple datasets from public databases to study the expressions of PSMA genes in multiple subtypes of BRCA together with interaction networks to trace potential coexpressed targets with PSMA genes.…”
Section: Introductionmentioning
confidence: 99%